Fresh validation of the low carbon development hypothesis under the EKC Scheme in Portugal, Italy, Greece and Spain - Balsalobre-Lorente, Daniel (2021)
The present study is in line with the United Nations Sustainable Development Goals (UN-SDGs) that address pertinent global issues. This study focuses on the need for access to clean and affordable energy consumption, responsible energy consumption, sustainable economic growth, and climate change mitigation. To this end, this paper evaluates the relevance of the renewable energy sector on the environmental Kuznets curve (EKC) framework in Portugal, Italy, Greece, and Spain for the period 1995–2015. As an econometric strategy, we adopt the use of panel data over the highlighted countries. In the first step, we apply the unit root test recommended by Levin, Lin, and Chu in conjunction with ADF-Fisher, and Phillips-Perron for robustness and consistency. We found that the variables used in this study are integrated I (1) in the first difference. In the second step, we apply the Pedroni cointegration test, and Kao Residual cointegration test, and we observe that the variables are cointegrated in the long run. The generalized least squares (GLS), the panel fully modified least squares (FMOLS), ordinary least squares robust (OLS), and panel quantile regression are considered in this research. The econometric results validate the assumption of the environmental Kuznets curve, i.e., and there is a positive correlation between income per capita and a negative effect of squared income per capita on carbon dioxide emissions. In contrast, we observe that renewable energy reduces CO2 emissions. Finally, we also find a direct connection between the urban population and the environmental degradation in the examined blocs. These results show that in Portugal, Italy, Greece, and Spain, more is required to achieve environmental sustainability in the respective countries growth trajectory. Further policy prescriptions are appended in the concluding section of this study.